Population genetic analysis of plant pathogenic fungi with emphasis on Fusarium species (2007)
The genus Fusarium is a major group of filamentous ascomycetous fungi with a global distribution. Fusarium species infect a wide range of hosts and produce a range of toxins which are harmful to animals and humans. Population genetics is the study of the behavior of a population in time and space. With the return of some of the destructive Fusarium diseases, the area of population genetics plays a vital role and seeks to understand the phenomenon. Phenotypic and molecular markers offer important information to interpret the population genetic structure of fungal plant pathogens. Vegetative compatibility group (VCG), mating population, mating type (MAT), female fertility and aggressiveness are the commonly used phenotypic markers in Fusarium. Molecular markers such as Restriction Fragment Length Polymorphism (RFLP), Random Amplified DNA Poymorphism (RFLP), Amplified Fragment Length Polymorphism (AFLP) and Simple Sequence Repeat (SSR) markers support and validate data based on phenotypic markers. Knowledge about the evolutionary forces that affect the genetic structure of pathogen populations such as mutation, population size, gene flow, reproductive system and selection may help to predict their evolution. This paper focuses on the population genetic structure of four destructive Fusarium species attacking the most important food crops in the world: F. verticillioides (corn), F. fujikuroi (rice), F. graminearum (wheat) and F. oxysporum (banana). Based on the literature data available, F. verticillioides, F. fujikuroi and F. graminearum are classified as medium risk pathogens in relation to durability of plant resistance while F. oxysporum f. sp. cubense is considered as a low risk pathogen. There is a dearth of information on the population genetics of F. fujikuroi. Among the five evolutionary forces, gene flow and reproduction/mating system are the most important parameters in Fusarium evolution. High VCG diversity and high variation in aggressiveness of sexually reproducing Fusarium species indicate the role of sexual reproduction in increasing genotypic diversity. VCG is a more appropriate marker in asexually reproducing F. oxysporum as this correlates with aggressiveness. F. verticillioides mating population A is prevalent in Philippine corn. Research on its population genetics is likely to contribute to better management of Fusarium diseases of agricultural crops.